Leak-Free Clear Corneal Incisions in Human Cadaver Tissue: Femtosecond Laser–Created Multiplanar Incisions. Issue 4 (July 2017) - Hill, James E.; Binder, Perry S.; Huang, Ling C.
Abstract : Objectives: To evaluate femtosecond (FS) laser–assisted leak-free clear corneal incisions (CCI) and paracentesis (P) in human eyes of deceased donors. Methods: Multiplanar CCI and P were created using an FS laser on human eyes of deceased donors (whole globe and corneal rims). Laser settings were programmed to multiplanar for CCI and single plane for P. Corneas were imaged by optical coherence tomography (OCT) and evaluated for leak by Seidel testing at various intraocular pressure (IOP) levels, and the wound was manipulated to mimic cataract surgery. Corneal endothelium cell damage and histological architecture were evaluated by microscopy. Results: The corneal incision software of the FS laser was used to create homogeneous CCI and P incisions. Morphological changes assessed by OCT and light microscopy/scanning electron microscopy showed consistent true multiplanar incisions with predefined intersecting planes. All Seidel testing was negative, indicating that FS laser–assisted incisions did not leak. Trypan blue stain of the endothelial surface showed limited cell damage from the FS laser incisions. Conclusions: The FS laser–created incisions corresponded well with the treatment plans, as evidenced by true multiplanar architecture. Incisions were sharply demarcated and demonstrated limited cell damage. No postprocedure leaking at extreme IOP or postcataract surgery–simulated conditions was noted. The FS laser may potentially reduce postoperative complications, such as infections that may be associated with CCI.